SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN MUTU PRMBRLAJARAN DI MADRASAH ALIYAH SWASTA IST'DADUL MU'ALLIMIEN KECAMATAN PENGABUAN PROVINSI JAMBI TAHUN PELAJARAN 2023/2024 - ALFIAH, ALFIAH (UNISAN JURNAL, 2024)
Academic supervision is carried out by the head of the Private Madrasah Aliyah Ist'dadul Mu'allimien Jambi is an effort to improve the quality of learning through coaching and guidance to teachers in planning learning, implementing the learning process, and evaluating student learning outcomes in order to achieve predetermined goals. This research uses a descriptive qualitative approach, namely the researcher only describes, analyzes phenomena, events and activities carried out in relation to academic supervision carried out by the head of Madrasah Aliyah Ist'dadul Mu'allimien Jambi with data collection techniques through: (1) Observation (2) Interview In-depth, and (3) Documentation Study. The selection of research informants used purposive techniques combined with Snowball Sampling. The data collected through the three techniques was then checked for validity by triangulation. Then analyzed by: (1) data reduction, (2) data presentation and (3) drawing conclusions. Based on the research results, the following findings can be concluded: Conclusion: academic supervision is one way to increase teacher professionalism in planning, implementing the learning process and evaluating student learning outcomes in order to improve the quality of learning so that both local and national educational goals can be achieved well.